Kajian Hasil Pembuatan Tiga Macam Ukuran Lubang Berbentuk Persegi Panjang Pada Tubuh Tungku Sekam - Darmasetiawan, H.; Irzaman, Irzaman; Demijati, Demijati; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Husk furnace is used for cooking fuel chaff with the aid of air flow in the furnace. One measurement of the husk furnace efficiency can be studied by varying the size of the primary air holes on the body of the furnace. In this study, a hole measuring 22 cm X 24 cm obtained by the rate of fuel consumption of 6.03 kg / hour of heat energy needed to boil water as much as 6 liters is 2575.00 kcal / h and 14.32% efficiency furnace. While in the hole measuring 22 cm X 8 cm and 22 cm X 16 cm, respectively 12.92% and 12.87% efficiency furnace, not significantly different. Keywords: chaff, husk furnace, ukuruan primary air hole, furnace efficiency